PATHOMORPHOLOGICAL CHANGE OF THE INTERNAL ORGANS AFTER THE GENERAL AND LOCAL COLD INJURIES - Oleinik, G.A. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
There were detected a lot of morphological changes of internal organs in patients after the general and local cold injuries.